2020
DOI: 10.1080/08897077.2019.1635963
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Screening and Brief Intervention for Unhealthy Alcohol use in Primary Care Waiting Rooms – a Pilot Project

Abstract: Background: In primary care, electronic self-administered screening and brief interventions for unhealthy alcohol may overcome some of the implementation barriers of face-to-face intervention. We developed an anonymous electronic self-administered screening brief intervention device for unhealthy alcohol use and assessed its feasibility and acceptability in primary care practice waiting rooms. Two modes of delivery were compared: with or without the presence of a research assistant (RA) to make patients aware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Social norms approaches are a potentially powerful and cost-effective way to promote behavior change [ 30 ] and may be incorporated into SBIs to help address the burden of addictive behaviors [ 31 , 32 ]. Social norms approaches include various distinct interventions, operationalized from different aspects of social norms theory e.g., social marketing, fear-based methods, and personalized normative feedback (PNF) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social norms approaches are a potentially powerful and cost-effective way to promote behavior change [ 30 ] and may be incorporated into SBIs to help address the burden of addictive behaviors [ 31 , 32 ]. Social norms approaches include various distinct interventions, operationalized from different aspects of social norms theory e.g., social marketing, fear-based methods, and personalized normative feedback (PNF) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods were used to study the feasibility of addictive disorder screening tests. Satisfaction questionnaires or a brief survey were the most commonly used methods ( Adam et al, 2019 , Bertholet et al, 2019 , Chan-Pensley, 1999 , Christoff et al, 2016 , Dyches et al, 1999 ; N. A. Johnson et al, 2013 , Nguyen et al, 2001 , Ríos-Bedoya and Hay, 2013 , Smith et al, 2011 , Wu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The computer version of AUDIT (Alcohol Use Disorders Identification Test) was considered easy-to-use and to understand ( Chan-Pensley, 1999 , Mulvaney-Day et al, 2018 ). The touchpad versions of SUBS (Substance Use Brief Screen) ( Bertholet et al, 2019b ) and TAPS (Tobacco, Alcohol, Prescription medication and other Substance use) (MyTAPS) were acceptable and easy-to-use but elderly people found this MyTAPS format more difficult ( Adam et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tablets for self-completion of clinic intake forms is increasing in many resource-rich settings; for instance, several clinical settings in the United States and Sweden have examined the use of digital screening and found that reporting of risk behaviors was comparable with more traditional screening methods [34,[47][48][49][50][51][52][53][54][55][56][57], and the digital screening over a wide range of patient characteristics was acceptable [58][59][60][61][62]. Audio computer-assisted self-interviewing (ACASI) has been associated with increased reporting of stigmatized behaviors such as forced sex, especially in Africa and rural settings [63].…”
Section: Digital Screeningmentioning
confidence: 99%